2012
DOI: 10.1371/journal.pone.0032696
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Betaproteobacterial Agent of Gill Epitheliocystis in Seawater Farmed Atlantic Salmon (Salmo salar)

Abstract: Epitheliocystis, a disease characterised by cytoplasmic bacterial inclusions (cysts) in the gill and less commonly skin epithelial cells, has been reported in many marine and freshwater fish species and may be associated with mortality. Previously, molecular and ultrastructural analyses have exclusively associated members of the Chlamydiae with such inclusions. Here we investigated a population of farmed Atlantic salmon from the west coast of Norway displaying gill epitheliocystis. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
106
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 34 publications
4
106
0
1
Order By: Relevance
“…The microsporidian has been found in high prevalence regardless of an actual diagnosis of clinical PGI in Norway; however, it was detected at 30 times greater abundance in fish with confirmed outbreaks than in unaffected fish (Matthews et al., ; Steinum et al., ). Additionally, Candidatus Branchiomonas cysticola has been identified as the main agent of epitheliocystis in Norway, and a relationship has been previously described between the epitheliocysit load and severity of PGI (Mitchell et al., ; Toenshoff et al., ). Some variation in opinion exists as to whether or not epitheliocystis is of significance, as some findings have been considered to be incidental during a study in Tasmania (Clark & Nowak, ).…”
Section: Introductionmentioning
confidence: 99%
“…The microsporidian has been found in high prevalence regardless of an actual diagnosis of clinical PGI in Norway; however, it was detected at 30 times greater abundance in fish with confirmed outbreaks than in unaffected fish (Matthews et al., ; Steinum et al., ). Additionally, Candidatus Branchiomonas cysticola has been identified as the main agent of epitheliocystis in Norway, and a relationship has been previously described between the epitheliocysit load and severity of PGI (Mitchell et al., ; Toenshoff et al., ). Some variation in opinion exists as to whether or not epitheliocystis is of significance, as some findings have been considered to be incidental during a study in Tasmania (Clark & Nowak, ).…”
Section: Introductionmentioning
confidence: 99%
“…The careful study of mixed epitheliocystis infections in Norwegian salmon (Steinum et al, 2010), pointing to an as yet unknown agent, led to the first identification of a beta-proteobacterium causing epitheliocystis (Toenshoff et al, 2012). Other species of beta-proteobacteria have since been identified in mixed epitheliocystis infections of gilthead seabream ( Sparus aurata ) (Qi et al, 2016; Seth-Smith et al, 2016), as have gamma-proteobacteria been identified in cysts from lake trout ( Salvelinus namaycush ) (Contador et al, 2016), Cobia larvae (Mendoza et al, 2013), and sharpsnout seabream ( Diplodus puntazzo ) larvae (Katharios et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One of these bacteria ( Candidatus Branchiomonas cysticola), associated with epitheliocystis on the gills of farmed Atlantic salmon in Norway, is not a member of phylum Chlamydiae, but a member of β-proteobacteria [18], [19], [20]. Hence, not all the epitheliocystis agents described from gills of different fish species are necessarily members of Chlamydiales.…”
Section: Introductionmentioning
confidence: 99%